Vibration Reduction for a Flexible Arm Using Magnetorheological Elastomer Vibration Absorber - Yushu Bian; Xuefeng Liang; Zhihui Gao (Shock and Vibration)
The application of the magnetorheological elastomer (MRE) to nonlinear vibration control for a flexible arm is investigated in this paper. A semiactive control method is suggested to reduce vibration via the internal resonance and the MRE. To establish a vibration energy transfer channel, a tuned vibration absorber based on the MRE is developed. Through adjusting the coil current, the frequency of the vibration absorber can be readily controlled by the external magnetic field, thereby maintaining the internal resonance condition with the flexible arm. By the perturbation analysis, it is proven that the internal resonance can be successfully established between the flexible arm and the MRE vibration absorber, and the vibration energy of the flexible arm can be transferred to and dissipated by the MRE vibration absorber. Through numerical simulations, virtual prototyping simulations, and experimental investigation, it is verified that the proposed method and the suggested MRE vibration absorber are effective in controlling nonlinear vibration of the flexible arm.